Design of non-linear controller for ocean wave energy plant. (November 2016) - Mishra, Sunil Kumar; Purwar, Shubhi; Kishor, Nand
Abstract: This paper proposes nonlinear control strategies for oscillating water column (OWC) wave power-take-off (PTO) systems. The system consists of Wells turbine, doubly fed induction generator (DFIG) and irregular wave models. This study considers a separately excited DC motor for emulating the Wells turbine. Plant emulation needs advanced control algorithms so that it reflects the practical behavior of actual plant under varying characteristics of ocean waves. Therefore, three non-linear controllers (NLC-1, 2 and 3) for OWC plant emulation and DFIG control have been designed using the Lyapunov stability theorem. The Pierson-Moskowitz and JONSWAP irregular wave models which represent realistic sea wave conditions have been applied for validating the proposed controllers. The OWC plant parameters such as Wells turbine flow coefficient, turbine torque and electrical output power has been compared between uncontrolled and controlled cases. The proposed rotational speed controller NLC-2 provides enhanced mean output power against uncontrolled operation of plant. The enhancement in output power is obtained as 25.14% and 39.24% for JONSWAP and Pierson-Moskowitz wave spectrum. Highlights: Controller design for emulation of Wells turbine characteristic. Maximization of output power of OWC power plants under aperiodic sea wave conditions. Regulation of the rotational speed to avoid the Wells turbine stalling.